Analisis Timbulan, Komposisi, Dan Penanganan Sampah Di Desa Langam Kabupaten Sumbawa Sebagai Dasar Perencanaan Pengelolaan Sampah Berbasis Masyarakat - Maitsa Fikri Nabila; Annisatun Nadzafah; Aryan Perdana Putra; Pramudya Bagas Utama; Eriza Riskita (Hexagon, 2025)
Langam Village in Sumbawa Regency has been designated as a pilot project for community-based waste management to address the challenges of ineffective waste management practices. This study aims to analyze the generation, composition, and current waste management practices in the village. A survey approach and quantitative analysis were employed to estimate the average daily waste generation, amounting to 2 tons per day. Organic waste dominated the composition, with food waste accounting for 33% and garden waste for 31%. Most households (76%) disposed of waste improperly due to limited facilities and a lack of awareness regarding environmentally friendly waste treatment. Further analysis highlights the urgent need for more efficient waste management through the 3R (Reduce, Reuse, Recycle) approach. Establishing 3R-based Waste Management Facilities (3R WMF) in each hamlet is recommended as a sustainable solution tailored to the geographic and social characteristics of Langam Village. The implementation of community-based waste management will not only reduce waste destined for the landfill but also raise public awareness and contribute to the achievement of Sustainable Development Goals (SDGs), particularly sustainable cities and communities